STRATEGI DIPLOMASI PERUSAHAAN MULTINASIONAL DALAM PENETRASI PASAR KE NEGARA BERKEMBANG (STUDI KASUS KOMATSU LTD DI INDONESIA) - Ichtiar Melia Cahyanti (HI 16 UMY 064, 2016)
*64 Multinational corporations (MNC) is an international or transnational company headquartered in one country but branch offices in various developed or developing countries Every Multinational Corparations has strategy to expansion their business. Komatsu Ltd as the big MNC in heavy equipment from Japan use their strategy to penetration in developing countries. The diplomatic Strategy of Komatsu Ltd are Cooperation with local industry in host country and using Komatsu Way as corporate culture. Keywords: Strategi, Multinational Corporations, Komatsu Ltd, Negara Berkembang,